Improving Students’ Ability in Writing Procedure Texts through Process Approach at MtsN Mojosari Mojokerto - R Heru Winardi (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2018)
The research was planned to improve students’ ability in writing procedure texts of first year of MTsN Mojosari Mojokerto through process approach. The subject of the study was class VIIA consisting of 32 studentsin 2015/2016 academic year. The finding of the study revealed that process writing approach was successful in improving the ability of MTsN Mojosari Mojokerto students in writing a procedure text. The number of the students who got score ≥ 60 increased from 6 students in Cycle 1, up to 28 students Cycle 2. The percentage of the students’ participation also increased from 66% in cycle 1, up to 77% in cycle 2. It means that process writing approach was successful in improving the first year students’ ability of MTsN Mojosari Mojokerto in writing a procedure text.